EBOLA DAN ANCAMAN KEAMANAN NON-TRADISIONAL DI ASEAN - Dewi Amelia Tresna Wijayanti (Sekretariat Jenderal DPR RI, 2014)
Global community currently faces the dangerous spread of Ebola endemic. This essay discusses the threat of Ebola outbreak as one of non-traditional security issues and the need for regional organizations to consider new concept in the multilateral cooperation to combat the threat. The results of this descriptive analysis reveals that the Ebola outbreak, as a non-traditional issue, is a catalyst for a more formal and institutionalized security cooperation amongst ASEAN countries.